Nonlinear structural behavior of flat-patterning ETFE cushion structures: Experimental observations and numerical simulations. (May 2017) - Hu, Jianhui; Yin, Yue; Chen, Wujun; Zhao, Bing; Yang, Deqing
Abstract: Ethylene tetrafluoroethylene (ETFE) cushion structures with the capacities of aesthetical appearance, excellent insulation and high strength-to-weight ratio have attracted considerable attention in recent years. Conventional ETFE cushion structures need fundamental form finding and cutting patterns, resulting in complex analysis and necessary strain compensation. For this reason, this paper focused on a new approach for form finding of flat-patterning ETFE cushions and corresponding nonlinear structural behavior. To achieve these goals, experiments for identifying mechanical properties of ETFE foils and structural behavior of a bubble prototype were carried out. Meanwhile, numerical simulations with Peirce model were performed to evaluate deformation, stress, total strain and plastic strain of flat-patterning ETFE cushions in the development of form finding. Comparisons between experimental and numerical results could obtain following conclusions. Deformation evolution with pressure increment indicated that nonlinear structural behavior was critical for understanding detailed structural behavior. The maximum stress and strain were larger than yield stress and strain, meaning that this form finding approach could consider hardening effects and thus get designed forms of ETFE cushions. The propagation mechanisms of stress and strain were characterized, which originated from edge middle area and propagated toward central area of the ETFE cushion. Moreover, it is found that plastic strain originated at 2000 Pa and reached a maximum value of 2.33% at 4000 Pa. In general, this study could provide useful observations and values for understanding nonlinear structural behavior of flat-patterning ETFE cushions in the development of form finding. Highlights: Experiments for material properties and structural behavior were carried out. Numerical simulations with Peirce model were done for flat-patterning cushions. Specific values and propagation mechanism of σ and ε evolution were obtained. Plastic strain originated at pressure of 2000 Pa and reached a maximum value of 2.57%. This form finding approach could consider hardening effect and get a designed form.